Bond-slip performance of seawater sea sand concrete filled filament wound FRP tubes under cyclic and static loads. (June 2023) - Bazli, Milad; Dorothea Luck, Johanna; Rajabipour, Ali; Arashpour, Mehrdad
Abstract: Adequate bond strength of concrete filled tubes is required to ensure full composite action and prevent premature bond failure before ultimate bending capacity is reached. This study investigates the bond strength and bond slip mechanisms of FRP tubes filled with seawater sea sand concrete (SWSSC) under static and cyclic axial loads using a push-out test. Glass and carbon fibre reinforced polymer (FRP) and two different diameters (100 mm and 165 mm) were tested to investigate the effect of changing parameters on the bond strength. Each group of specimen was tested under static load (SL) and various different cyclic loading (CL) regimes. An ANSYS FE model was created to simulate a static pushout test for FRP SWSSC composites under varying parameters to quantify the induced tube and confinement stress. Confinement and accumulated damage were found to be the two main factors determining the change in bond strength between cyclic and static load conditions. The high active confinement of the smaller diameter GFRP tubes resulted in a slight increase in bond strength for most samples under CL. The larger diameter CFRP tubes generally exhibited a slight drop in bond strength under CL due to the more pronounced effects of accumulated interface damage.